2023
DOI: 10.1002/hipo.23585
|View full text |Cite
|
Sign up to set email alerts
|

Granule cells perform frequency‐dependent pattern separation in a computational model of the dentate gyrus

Selena Singh,
Suzanna Becker,
Thomas Trappenberg
et al.

Abstract: Mnemonic discrimination (MD) may be dependent on oscillatory perforant path input frequencies to the hippocampus in a “U”‐shaped fashion, where some studies show that slow and fast input frequencies support MD, while other studies show that intermediate frequencies disrupt MD. We hypothesize that pattern separation (PS) underlies frequency‐dependent MD performance. We aim to study, in a computational model of the hippocampal dentate gyrus (DG), the network and cellular mechanisms governing this putative “U”‐sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…One area of promise for identifying predictors may be behavioural tasks that are hypothesised to probe lower-level DG neural computational functioning, such as MD. In a previous study, we hypothesised that PS may underlie MD performance [44], based on two lines of evidence for the DG’s involvement 1) during MD [37, 65], and 2) in PS [33, 34]. Interestingly, a pilot study of the effects of lithium therapy in BD on MD performance demonstrated that lithium therapy significantly improved MD performance in LRs only [39].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One area of promise for identifying predictors may be behavioural tasks that are hypothesised to probe lower-level DG neural computational functioning, such as MD. In a previous study, we hypothesised that PS may underlie MD performance [44], based on two lines of evidence for the DG’s involvement 1) during MD [37, 65], and 2) in PS [33, 34]. Interestingly, a pilot study of the effects of lithium therapy in BD on MD performance demonstrated that lithium therapy significantly improved MD performance in LRs only [39].…”
Section: Discussionmentioning
confidence: 99%
“…N indicates the number of cells per population. This circuit diagram was adapted from our previous paper [44]. D) The pattern separation (PS) performance of these networks were then assessed, by presenting the network with a series of partially overlapping PP input patterns, and assessing whether the resulting output patterns were less correlated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations